Spiritual guidance according to al-Ghazali and it's relationship with the effectiveness of counseling: case study at the counseling centre of Islamic religious council of Negeri Sembilan - Salasiah Hanin Hamjah, (Penerbit Universiti Kebangsaan Malaysia, 2010)
Application of spiritual elements in counseling is vital and has been recognized widely by counseling practitioners nowadays. This is because most of the problems faced by human being are not only due to the external factors but also the spiritual aspects especially those related to oness heart feelings and emotions. Hence, this research attempts to study whether al-Ghazallss spiritual guidance is implemented in the counseling sessions at Counseling Centre of Islamic Religious Council of Negeri Sembilan, Malaysia. Besides, this study also examines the relationship between the spiritual guidance from al-Ghazaliss perspective and the effectiveness of counseling. This study also examines the difference between marital status with the counselors preferences to apply al-Ghazallss spiritual guidance in counseling. This study uses survey as its research design and questionnaires as the main instrument. 30 respondents were selected purposively among clients who have experienced counseling sessions at Counseling Centre of Islamic Religious Council of Negeri Sembilan, Malaysia. The result of the study shows that some aspects of al-Ghazaliss spiritual guidance are implemented in the counseling sessions especially those on the concept of purification of soul. The findings also show that there is a significant relationship between spiritual guidance from al-Ghazaliss perspective and the effectiveness of counseling (r = 0.469 ; p < 0.01). Besides, the research also highlights a difference between marital status with the counselors preferences to apply al-Ghazaliss spiritual guidance in counseling (t = 3.450; p < 0.05).